A Decade of Pollen Phosphoproteomics - Klodová, Božena; Fíla, Jan (International journal of molecular sciences, 2021)
Angiosperm mature pollen represents a quiescent stage with a desiccated cytoplasm surrounded by a tough cell wall, which is resistant to the suboptimal environmental conditions and carries the genetic information in an intact stage to the female gametophyte. Post pollination, pollen grains are rehydrated, activated, and a rapid pollen tube growth starts, which is accompanied by a notable metabolic activity, synthesis of novel proteins, and a mutual communication with female reproductive tissues. Several angiosperm species (Arabidopsis thaliana, tobacco, maize, and kiwifruit) were subjected to phosphoproteomic studies of their male gametophyte developmental stages, mostly mature pollen grains. The aim of this review is to compare the available phosphoproteomic studies and to highlight the common phosphoproteins and regulatory trends in the studied species. Moreover, the pollen phosphoproteome was compared with root hair phosphoproteome to pinpoint the common proteins taking part in their tip growth, which share the same cellular mechanisms.
Keywords: pylová láčka; rostlinné proteiny; Proteome; Plant Proteins; Pollen Tube; Pollination; Proteomics; opylení; Phosphoproteins; fosfoproteiny; proteomika; root hair; male gametophyte; proteom; phosphoproteomics; pollen tube; kinase motif; signal transduction